2018
DOI: 10.1111/rda.13356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a bovine visual pregnancy test for the detection of pregnancy‐associated glycoproteins in sheep

Abstract: Contents As sheep produce similar pregnancy‐associated glycoproteins (PAGs) to cattle, a commercially available bovine visual pregnancy test based on the detection of PAGs (visual‐PAG‐test) was evaluated in sheep. The test was performed with whole blood (WhB), plasma (P) and serum (S) of 163 pregnant and 153 non‐pregnant ewes. Additionally, 11 pregnant ewes were tested weekly from day 14 to 49 of gestation and monthly from day 60 to day 149. Ten ewes were sampled weekly from the date of lambing until day 63 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
3
11
1
Order By: Relevance
“…In agreement with this report, the accuracy of transabdominal ultrasonography was determined to be 96% in the present study. The sensitivity determined for rapid visual PAG ELISA (97.6%) in the present study was in agreement with sensitivities previously reported in Santa Ines ewes 26-30 days after mating (Chaves et al, 2020), in Dorper, Shropshire, Hampshire and crosbred (Dorset x Polypay) sheep 30-90 days after mating (Roberts et al, 2019) and in German Blackhead and Merino sheep in mid-pregnancy (range: 71-120 days) (Steckeler et al, 2018). Furthermore, sensitivities similar to the sensitivity determined for the rapid visual PAG ELISA in the present study were reported for the "Idexx visual pregnancy test" in Santa Ines ewes 30 days after laparoscopic insemination (Chaves et al, 2017) and for the "Idexx bovine pregnancy test" in Corriedela and Ile de France x Texel sheep throughout pregnancy (Rovani et al, 2016).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with this report, the accuracy of transabdominal ultrasonography was determined to be 96% in the present study. The sensitivity determined for rapid visual PAG ELISA (97.6%) in the present study was in agreement with sensitivities previously reported in Santa Ines ewes 26-30 days after mating (Chaves et al, 2020), in Dorper, Shropshire, Hampshire and crosbred (Dorset x Polypay) sheep 30-90 days after mating (Roberts et al, 2019) and in German Blackhead and Merino sheep in mid-pregnancy (range: 71-120 days) (Steckeler et al, 2018). Furthermore, sensitivities similar to the sensitivity determined for the rapid visual PAG ELISA in the present study were reported for the "Idexx visual pregnancy test" in Santa Ines ewes 30 days after laparoscopic insemination (Chaves et al, 2017) and for the "Idexx bovine pregnancy test" in Corriedela and Ile de France x Texel sheep throughout pregnancy (Rovani et al, 2016).…”
Section: Resultssupporting
confidence: 92%
“…The presence of PAGs in the maternal circulation allows for an early diagnosis of pregnancy in cows Akköse and Çebi Şen, 2019), sheep (Uçar et al, 2018;Alkan et al, 2020) and goats (Gonzalez et al, 1999;Tandiya et al, 2013 Xie et al (1991) detected immunological and structural similarities between ovine and bovine PAG molecules, it has also been reported that bovine and ovine PAGs can exhibit spatially and temporally distinct expression patterns during pregnancy at species or breed level (Green et al, 2000;Lobago et al, 2009;Mercadante et al, 2013). PAG ELISA pregnancy tests commercially validated for cattle have been used in various Brasilian and European sheep breeds (Rovani et al, 2016;Chaves et al, 2017;Steckeler et al, 2018). It is stated that PAG profiles in the peripheral blood can vary between sheep breeds; therefore, determining the specific PAG profile of breeds native to Turkey is important for improved reproductive management (Kaplan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules are present in maternal plasma of sheep in concentrations detectable with RIA methods as early as 18-20 days after conception, [3,[11][12][13][14][15][16] and by the enzyme immune assay (EIA) method [17][18][19], as well as in other species of ruminants [1,[20][21][22]. Throughout pregnancy, PAG concentrations in these species differ according to the breed, fetal number, sex and birth weight [3,[23][24][25][26][27][28][29], as in other ruminants [30].…”
Section: Introductionmentioning
confidence: 99%
“…PAG levels can also be measured in whole blood, serum, plasma, and milk (6,46). In addition to the ELISA method, some researchers have studied PAG levels using the RIA method (6,51).…”
Section: Tab 1 Intergroup Comparison Results Of Pregnancy Proteins (Ng/ml)mentioning
confidence: 99%
“…This study is compatible with existing research as it used the ELISA method to determine the PAG level by taking blood for measurement starting from day 30 of pregnancy. Studies have shown that the bovine PAG kit can be used for PAG measurement in sheep (39,46). This is because PAG molecules released from trophoblast cells in the placenta of ruminant cattle and sheep have a similar molecular structure, and the cDNA encoding PAG has 86% nucleotide similarity (39).…”
Section: Tab 1 Intergroup Comparison Results Of Pregnancy Proteins (Ng/ml)mentioning
confidence: 99%